Cross-cultural attitudes toward generative AI in Art: Implications for sustainable creativity in the U.S., Japan, and China - Suomiya Bao (Sustainable Futures, 2025)
This study investigates the perceptions and attitudes toward generative AI art across three major global economies: the United States, Japan, and China. As leaders in AI development, these countries exhibit distinct viewpoints regarding the integration of AI into the creative process. The investigation was conducted using an online questionnaire, which gathered responses from participants in the three countries. The survey consisted of questions that assessed participants’ experiences with AI tools, their views on AI-generated art in various forms, and their ethical concerns regarding its use. The results indicate that participants in China are generally more optimistic about the value of AI-generated art, prioritizing the quality of the final product over ethical concerns. In contrast, participants in the U.S. and Japan emphasize the importance of human creativity and express skepticism about AI art, primarily due to ethical concerns such as misinformation and intellectual property issues. While Chinese participants focus on data privacy and intellectual property protection, U.S. participants are more concerned with misinformation and fake content. Japan, despite having the least experience with AI tools, presents attitudes that often fall between the positions of the U.S. and China. This study provides valuable insights into cross-cultural differences in attitudes toward AI art, offering guidance for educators, policymakers, and AI developers on integrating AI into the art and design sectors in a sustainable, ethical, and culturally adaptive manner.